Prevalence of mastitis causing organism and their antibiotic resistance pattern in dairy farms - Kour, Gurleen; Chandra, Mudit; Kaur, Gurpreet; Narang, Deepti; Gupta, D K; Arora, A K; Sharma, N S (Indian Journal of Dairy Science, 2017)
In the present study, prevalence of the mastitis causing organisms was examined. A total of 102 milk samples from clinical and subclinical mastitis cases were collected and processed for isolation of bacteria using Brain Heart Infusion Agar, Eosin Methylene Blue Agar, Mac Conkey’s Lactose Agar, Baird Parker Agar supplemented with egg-yolk tellurite emulsion, Edward’s medium and Blood Agar and a total of 50 samples yielded bacterial growth. Out of these 50 samples, 16 (32%) had single bacterial growth whereas rest of the 34 (68%) had mixed bacterial growth. All the organism were subjected to cultural, morphological, biochemical tests and genus specific PCR for confirmation and it was found that a total of 43 (41.74%) Staphylococcus, 15 (14.56%) Streptococcus, 26 (25.24%) E. coli and 19 (18.44%) Klebsiella were isolated. All these isolates were screened for their antimicrobial resistance using antibiotic sensitivity test against commonly used 23 antibiotics. On the basis of zone of inhibition it was observed that overall chloramphenicol (88%) was found most sensitive followed by gentamicin (74%), co-trimaxazole (66%), ciprofloxacin (62%), ofloxacin (60%), gatifloxacin (58%), cephalexin (56%) and sparafloxacin (52%) whereas maximum resistance was observed against penicillin (96%) followed by methicillin, amoxicillin and teicoplanin (82%) and streptomycin (80%). Thus, from the study it could be concluded that Staphylococcus was the most common mastitis causing organism and chloramphenicol, gentamicin, co-trimaxazole and ciprofloxacin were found to be most sensitive antibiotics. Also, the presence of methicillin resistance in the Staphylococcus strains identified in the present study.